Single-electron induced surface plasmons on a topological nanoparticle - G. Siroki (Nature Portfolio, 2016)
The surface states in topological insulators are delocalised and immune to imperfections. Here, the authors show that single electrons in topologically protected surface states on a nanoparticle can create a surface charge layer that screens the particle, mediating interaction between bulk phonons and light, giving an additional absorption peak.